PENERAPAN MODEL TANGKI DENGAN TIGA TANGKI SUSUNAN PARALEL UNTUK TRANSFORMASI DATA HUJAN MENJADI DATA DEBIT (STUDI KASUS PADA INFLOW WADUK SELOREJO DAN WADUK LAHOR) - ., Rahman (Media Teknik Sipil, 2011)
An inspiriting factor in making a hydrology model especially rain water transformation datamodel to become debit data is debit accumulation handicap. Sugawara cube model is one of conceptualmodels which has concept rain water stream process become a river stream is analogized as astream through the parallel cube. The approach of cube model can be done in seri, parallel, or themixed.Modeling simulation processes will produce parameters or coefficients of cube model makethe cube model and its parameters can show the condition of river stream area.Three parallel cubes have 14 chosen parameters. The solution is optimizing it to get optimalparameter that can represent a DAS modeled. Algoritma Genetik can be used in the optimizationprocess; it shows the effectiveness and the capacity to determine parameter. The result of theanalysis of 2 DAS shows that the cube model with 3parallel cube represents the correlation ofclimate data and water debit with good process., model gives good trend in fluctuate debit of water.This optimizing technique is covered in Mantlab programming language which is ready to be developedin another DAS.Key word : Hydrology model, 3 Parallel cube model, Parameter, Optimize, Algoritma Genetik